Neuropathic pain and quality of life after wide local excision and sentinel lymph node biopsy for melanoma: a multicentre study. Issue 2 (April 2017) - Thomson, Collette H.; Cassell, Oliver; Peach, Howard; Holloway, Samantha; Garioch, Jennifer; Moncrieff, Marc
Abstract : Wide local excision and sentinel lymph node biopsy is the mainstay of treatment for patients with melanoma. As survival outcomes improve, longer term quality of life questions become more pertinent and this study aims to assess the factors which may play a role following surgery. A total of, 221 patients who underwent wide local excision and sentinel lymph node biopsy for melanoma (AJCC stage I and II) were recruited from three UK centres. These patients completed a patient outcome questionnaire, which included demographic and treatment data as well as quality of life and pain questionnaires. Pain was the only significant factor influencing the quality of life with a negative correlation seen between pain and quality of life scores ( P <0.001). In total, 34% of patients reported pain at their surgical site and four (1.8%) patients scored as high risk for neuropathic pain. Patients experiencing pain were significantly younger that those not reporting pain (median 55.0 vs. 63.5 years, P <0.001). Length of time since surgery did not correlate with pain nor quality of life scores. Our results suggest that following this common procedure a sizeable proportion of patients experience pain and poorer quality of life which does not improve with time. The level of pain experienced is clinically significant and merits evaluation and treatment in this group of patients who are increasingly surviving their melanoma diagnosis. Further investigation into potential prophylactic measures is suggested.